THE IMPLEMENTATION OF ARCS BASED PROBLEM BASED LEARNING IN INCREASING MATHMATICS LEARNING MOTIVATION - Kholid Kholid (AL IBTIDAIYAH: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2020)
This classroom action research is to describe "Efforts to Improve Student Learning Outcomes of Class XI IPA 2    SMA Negeri 1 Senori Tuban Dalam In Linear Program Material through Problem Based Learning Model with ARCS motivation strategy". This classroom action research is designed to be carried out in 2 cycles. Each cycle consists of four stages that must be followed, namely planning, acting / acting, observing and reflecting. The observation result in cycle II shows that the students' motivation to learn mathematics after the application of the Problem Based Learning model with the ARCS motivation strategy has increased. In the second cycle of observation, 64.29% of students had high motivation. The percentage of all indicators has increased from cycle I to cycle II.